Evaluating Language Curriculum Management in International Class Programs: A CIPP Model Perspective - Sari Famularsih; Abdul Syukur; Alfin Rosyidha; Safinatul Fitriah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to evaluate the language aspects in the curriculum management for the International Class Program (ICP) at UIN Salatiga and UINSI Samarinda from an institutional perspective. It is qualitative research involving several informants, such as the ICP Directors, the Head of the Study Program, and the lecturers. Method: To gather the data, the researchers used observation, interview, and documentation. After collecting the data, the researchers perform analysis to answer research questions. In analyzing the result, the researchers refer to three stages: data reduction, data display, and conclusion (drawing/ verifying). Results: The results of the evaluation in the curriculum management of the ICP are analyzed using the CIPP evaluation model assessment, which comprises Context Evaluation, Input Evaluation, Process Evaluation, and Product Evaluation. Novelty: Through this assessment model, the researchers can find the existing curriculum that can support the language learning aspects and the opportunities for the ICP management to improve the curriculum on language aspects of learning to achieve the expected outcome.